The Effectiveness of the Learning Management System of Saqural Learning Application on the Scientific Interpretation Learning Outcomes (Jurnal Pendidikan IPA Indonesia, 2021)
This study aims to obtain an effective BERSAQURAL Learning Management System on the learning outcomes of BERSAQURAL interpretation through digital literacy. This study is a quantitative type with One-Group Pretest-Posttest Design. This study population was 90 third-semester science education students at the Faculty of Teacher Training and Education IAIN Salatiga who participated in a science interpretation course. The sample in this study was purposive sampling, and one group is 30 students. The data collection instrument was pretest and posttest questions of the BERSAQURAL interpretation of water. The results showed that: (1) the BERSAQURAL learning management system in the dashboard consists of the navigation menu, interpretation of science, nature, al-Qur’an, e-Problem Based Learning, evaluation, explore material, user, my profile, settings, and logout, (2) BERSAQURAL learning management system is effective on learning outcomes of BERSAQURAL interpretation through digital literacy based on the Wilcoxon test (t count -4.802, p = 0.00 0.05). Research results of learning management system BERSAQURAL have novelty, a distance learning media (online) with open-access material as digital literacy, connecting LMS E-PBL Berketemu Ilmiah (e-pblberketemuilmiah.id) integrated with a plagiarism checker to educate honesty. There are rewards from users of the BERSAQURAL Learning Management System in the stars or on the trending menu.